Autodesk Inventor Instruction for Technical Drawing Teachers in High School/Vocational Schools - Rolan Siregar; Asy'ari Firdaus; Eva Novianti; Ade Supriatna (Fakultas Teknik Universitas Darma Persada, 2024)
The objective of this training is to enhance the proficiency of high school/vocational high school teachers in the creation of technical drawings using Autodesk Inventor, a software that is utilized for 3D modeling, structural strength simulation, motion animation, and other engineering analyses. The Faculty of Engineering, Darma Persada University conducted this training on February, both online and offline. The training method encompasses theory, direct practice, and evaluation through pre-tests and post-tests. The results of the training demonstrated a decrease in the teachers' comprehension of the fundamental concepts and the application of Autodesk Inventor in engineering education. The documentation and evaluation of this program can serve as a reference for the development of similar training in the future.